2013 Evaluation of Non-Irrigated Early-Maturing Cotton Varieties in Jay, Florida - Darcy E. P. Telenko; Michael Donahoe (EDIS)
This report includes a summary of the 2013 early-season cotton Official Variety Trial in Jay, Florida. It shows the performance of 11 cotton varieties. This data represents only one year and one location, and readers are cautioned that test results should be considered over several locations and years before final conclusions are valid. This 5-page fact sheet was written by Darcy Telenko and Michael Donahoe, and published by the UF Department of Agronomy, January 2014.